2020
DOI: 10.1080/13102818.2020.1816216
|View full text |Cite
|
Sign up to set email alerts
|

AMMI analysis of genotype × environment interaction on grain yield of sesame (Sesamum indicum L.) genotypes in Iran

Abstract: In this study, we investigated the effect of genotype  environment interaction (GEI) on the grain yield of 15 different sesame genotypes on four test areas (Arak, Birjand, Karaj and Shiraz) in two years (2017-2018). We observed significant differences in all sources of combined variance analysis. The interaction items in AMMI (additive main effects and multiplicative interactions) analysis of variance were divided into three parts, in which the interaction principal components IPC1 and IPC2 items justified ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…3), the superior genotypes were G5 > G1 and G, and where located on the right side of the graph and close to zero in terms of the IPC1 axis. These results are similar to the observation reported by Movahedi et al [16].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…3), the superior genotypes were G5 > G1 and G, and where located on the right side of the graph and close to zero in terms of the IPC1 axis. These results are similar to the observation reported by Movahedi et al [16].…”
Section: Discussionsupporting
confidence: 93%
“…"AMMI is one of the best analyses for testing genotype stability. In this study, the analysis of 18 Common bean genotypes on three test locations in the grain yield trait gave similar Ftest results to the AMMI analysis performed" by Movahedi et al [17]. Yan et al, [18] pointed out that genotypes with IIPC scores near zero are more representative of an average environment.…”
Section: Discussionsupporting
confidence: 78%
“…However, the eigenvalues of the first two principal components were greater than one, explaining the interaction in 67.5%. Thus, the analysis of AMMI with PC1 seems appropriate and can explain the effect of the interaction, as it has been shown in G×E interaction studies in tomato (Ceballos-Aguirre et al, 2020) and sesame (Movahedi et al, 2020). There are no studies on cape gooseberry in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gauch et al (2008), this model has shown results with a clear agronomic meaning and has been effective due to its ability to capture the G×E interaction. At the same time, this model facilitates the identification of mega-environments and allows breeders to interpret the data and make reliable decisions in the selection of superior genotypes for each environment (Zobel et al, 1988;Gauch et al, 2008;Movahedi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that this technique is beneficial in the results of their research on this subject. (Gauch, 2006;Xu et al, 2014;Movahedi et al, 2020;Khan et al, 2021;Yaşar, 2023).…”
Section: Gge Biplot Analysismentioning
confidence: 99%